2017
DOI: 10.1016/j.jacc.2017.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Left Ventricular Filling Pressure by Echocardiography

Abstract: Echocardiographic assessment of LV filling pressure is feasible and accurate. When combined with clinical data, it leads to a more accurate diagnosis, regardless of LVEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
275
4
15

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(309 citation statements)
references
References 28 publications
15
275
4
15
Order By: Relevance
“…A recent study comparing the correlation between E/e′ ratio, LAVI, and LVFP found that correlation of the LAVI with LVFP (r=0.23) was weaker than that of E/e′ (r=0.65). 41 In addition, the measurement of LAVI may be inaccurate in patients with atrial fibrillation (15% incidence in our study sample). An inaccurately measured LAVI would not correlate with LVFP and therefore the association between LAVI and postoperative AKI may be weakened.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A recent study comparing the correlation between E/e′ ratio, LAVI, and LVFP found that correlation of the LAVI with LVFP (r=0.23) was weaker than that of E/e′ (r=0.65). 41 In addition, the measurement of LAVI may be inaccurate in patients with atrial fibrillation (15% incidence in our study sample). An inaccurately measured LAVI would not correlate with LVFP and therefore the association between LAVI and postoperative AKI may be weakened.…”
Section: Discussionmentioning
confidence: 74%
“…For this validation, a recent multicenter study evaluated the accuracy of estimating LVFP by echocardiography. 41 In their results, an average E/e′ ratio was modestly correlated with invasively measured LVFP (r=0.65). The accuracy of diagnosis of elevated filling pressure by echocardiographic index was good, with an overall accuracy of 87%, although the accuracy was less reliable with normal EF (84%) compared with 91% with a decreased EF.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Two recent multicenter studies compared echocardiographic estimates of LV filling pressures against invasive measurements by cardiac catheterization and reported high feasibility and good accuracy irrespective of LV function, especially when combined with clinical data. 6,7 These studies were performed by investigators who constituted the core of the guidelines writing group and have extensive specific expertise in the evaluation of diastolic function by echocardiography.…”
mentioning
confidence: 99%
“…17 We thus speculate that any factors could have altered the relationship between LVMDP and E/e′, as between τ and e′, which we have already stated. Accordingly, we tested the determinants of E/e′ and found that not only LVMDP but also LVMI were independent determinant of E/e′.…”
Section: Advance Publication By-j-stagementioning
confidence: 51%